Occupational choice and the private equity premium puzzle - Thomas Hintermaier; Thomas Steinberger (Institute for Advanced Studies (IHS), 2002)
This paper suggests a solution to what has become known as the private equity premium puzzle (Moskowitz and Vissing-Jorgensen (2002)). We interpret occupational choice as a dynamic portfolio choice problem of a life-cycle investor facing a liquidity constraint and imperfect information about the profitability of potential businesses. In this setting, becoming an entrepreneur is equivalent to investing in non-traded private equity capital subject to transaction costs. We model the return on private equity as the sum of two components, the individual ability of the entrepreneur and idiosyncratic business risk. Information is imperfect, because only entrepreneurs observe their own business risk realizations. Using numerical techniques we find that the model generates the observed return structure for private equity using standard CRRA-preferences and fully rational expectations.
Keywords: G11; D91; 330; portfolio choice; life-cycle models; private equity; Portfolio-Management; Privater Haushalt; Lebenszyklus; Kapitalbeteiligung; Private Equity; Kapitalertrag; Entrepreneurship-Ansatz; KMU; Theorie